Artificial Intelligent (AI), Effectuation Theory, and International Opportunity: A Powerful Approach to Global Entrepreneurship - Sathiswaran A/L Uthamaputhran; Kiran Kumar Thoti; Yusrinadini Zahirah Binti Md. Isa@Yusuff; Wahidah Shar; Wan Nur Fazni Wan Mohamad Nazarie (Journal of Harbin Engineering University (JHEU), 2024)
A potent strategy for international business at the crossroads of Artificial Intelligence (AI), Effectuation Theory, and Cross-Border Opportunities. The rapid development of AI technologies has changed several fields, including business, by opening previously inaccessible opportunities. However, Effectuation Theory provides an alternative viewpoint on entrepreneurs' decision-making processes by placing an emphasis on making do with what's at hand and developing new opportunities through repeated trial and error. Entrepreneurs can improve their processes of opportunity discovery and exploitation in a global setting by merging AI with Effectuation Theory. Entrepreneurs can now analyse massive volumes of data, see trends, and make educated judgements about market entrance strategies and business models with the use of AI-powered tools like natural language processing, machine learning, and data analytics. This document summarises the most important aspects of this effective strategy for international business. Specifically, it looks at how AI can improve the effective logic's four stages—finding a tolerable loss, picking a good partner, making a valuable contribution together, and capitalising on a lucky break. In addition, it investigates how AI might improve the speed and accuracy with which foreign business opportunities are spotted by reducing the risks normally associated with doing business abroad. This study adds to the literature by outlining a complete framework for studying international opportunity in the context of artificial intelligence, effectuation theory, and other related fields. For business owners and government officials, it provides actionable advice on how to leverage AI to seize overseas opportunities, encourage entrepreneurship on a global scale, and propel economic expansion. In conclusion, this research promotes the strategic use of AI in the entrepreneur's toolkit so that rising global markets' full potential can be realised and the difficulties of the global business landscape can be successfully navigated.